KOLABORASI SISTEM INFORMASI DAN SISTEM PENDUKUNG KEPUTUSAN UNTUK MENGHASILKAN PENILAIAN SASARAN KERJA PEGAWAI BAGI DOSEN - Heribertus Ary Setyadi; Agung Nugroho (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Employee performance appraisal system in a systematic way that combines a Goal-setting Employee Work with behavioral assessment work. SKP has a weight of 60% while 40% work behavior. Performance appraisal is based on the size of the level of achievement that nmeliputi SKP aspects of quantity, quality, time and / or costs. Ratings are not limited to the assessment but also assessment through behavioral observations pelayahan work which includes orientation, integrity, commitment, discipline, teamwork and leadership. Collaborative Information Systems and Decision Support Systems made in this study aims to assist officials in evaluating performance targets structural work and work behavior. SKP which is the value of the activities of Tri Dharma data is entered every time the activities included an assessment has no decree or activity has been completed. From the data that has been entered is then SKP can be printed when needed with the appropriate data. Assessment work behaviors created using AHP, some weighting criteria for lecturers will vary with structural officials. The use of AHP method aims for objectivity of the assessment work behavior to be more secure. The system was created using Visual Basic and Access as the database. Phase analysis is done is to analyze the running system, the system uses PIECES weakness analysis and requirements analysis system. In the design of the system is made usecase diagrams, activity diagrams, class diagrams, design input and database design.Keywords: Information Systems, Decision Support Syste, SKP, AHP.